SISTEM IDENTIFIKASI PENYAKIT TANAMAN PADI DENGAN MENGGUNAKAN METODE FORWARD CHAINING - Ika Arthalia Wulandari; Aristoteles Aristoteles; Radix Suharjo (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Rice plant diseases can be identified from their symptoms. To find out exactly the rice plant disease, it will need agricultural experts. Numbers and distributions of agricultural expert are very limited and they cannot overcome the problems optimally, so that a system containing knowledge as what experts do is required. This research was to design web-based experts system by using forward chaining method and certainty factor. Data processed in this system were 16 diseases and 26 of disease symptoms. This system which was developed had superiorities and easiness in accessing it, user friendly and displaying certainty levels from diagnosis results with 81% of customerâ€™s satisfaction.Â Kata Kunci â€“experts, expert system, forward chaining, rice plant diseases.